THE ROLE OF SECURITY SECTOR REFORM IN AFRICA DEVELOPMENT - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Security sector reform is the transformation of the security system, which includes all of its actors, their roles, responsibilities and actions, so that it is managed and operated in a manner that is more consistent with democratic norms and sound principles of good governance, and thus contributes to a well-functioning security framework (Ball, 2011). Responsible and accountable security forces reduce the risk of conflict, provide security for citizens and create the right environment for sustainable development. The overall objective of SSR is to contribute to a secure environment that is conducive to development (Brzoska, 2013). The focus for international actors should be to support partner countries in achieving four overarching objectives: Establishment of effective governance, accountability and oversight structures in the security system; improved delivery of security and justice services; development of local leadership and ownership of the reform process; sustainability of justice and security service delivery (Bryden and Hänggi, 2010).